Two new species of Strongylium Kirby (Coleoptera: Tenebrionidae) from Xizang, China - Wu, Bo; Yuan, Cai-Xia (Zootaxa, 2026)
Two new species of the genus Strongylium Kirby, 1819 from Xizang, China were discovered and are described under the names of S. (s. str.) beibengense sp. nov. (Mêdog) and S. (s. str.) medogense sp. nov. (Mêdog and Bomi). Illustrations of the habitus and diagnostic features are presented.